Training of Personnel in the Field of Physical Education and Sports (Eurasian Journal of Learning and Academic Teaching, 2022)
In this article, the organization of physical education and sports in the educational institutions of the Republic of Uzbekistan, the issues of training specialists in their purposeful implementation, the goals and tasks, the history of development, the features of the development of the physical culture system during the former union and the years of independence, in the following years the reforms carried out in the physical culture system and their positive effects are widely disclosed